NILAI-NILAI ISLAMI PADA MATERI SENI RUPA DI SMP PERGURUAN ISLAM AR RISALAH PADANG - PUTRI ANDAYANI, Drs. Wisdiarman, M.Pd., Drs. Abd. Hafiz, M.Pd. (Universitas Negeri Padang, 2018)
The purpose of this research were (1) to describe the contents of fine arts material at SMP Perguruan Islam Ar Risalah Padang, (2) to find out the Islamic values in the fine arts material at SMP Perguruan IslamArRisalah. The data source of this research is fine arts teaching materials. As for data collection through observation, documentation and interviews. The research findings based on the suitability table of material in the quadra book contained 91% of material that was in accordance with Islamic law and 9% of the material was not in accordance with Islamic law. Whereas in the book of the Ministry of Education and Culture there are 62.5% of material that is in accordance with Islamic law and 37.5% of material is less in accordance with Islamic law.Kata kunci: Nilai-nilai Islami, Materi Seni Rupa